The Urgency of Zikir in Modern Life - Muchamad Toif Chasani (Formosa Journal of Multidisciplinary Research, 2022)
Remembrance is an attempt to approach humans as a servant to God Almighty. In this paper, we will examine the form of remembrance in its urgency in modern life. This study uses a type of library research, data sources are collected from primary sources and secondary sources, then analyzed using content analysis. The results of the study stated that there are ways of remembrance in ginger (loud) and sirri (slow) ways. While the forms of remembrance found in the Qur'an and Hadith include istighfar, tahmid, tasbih, tahlil, takbir, prayer, hauqalah, prayer. the practice of remembrance in the phenomenon of modern life there is a salawat remembrance assembly.